Application of 15N tracing for estimating nitrogen cycle processes in soils of a constructed wetland. (15th September 2020) - Jahangir, M.M.R.; Fenton, O.; Carolan, R.; Harrington, R.; Johnston, P.; Zaman, M.; Richards, K.G.; Müller, C.
Abstract: Integrated Constructed Wetlands (ICW) area technology for the attenuation of contaminants such as organic carbon (C), nitrogen (N), phosphorous (P) and sulphur (S) in water coming from point or diffuse sources. Currently there is a lack of knowledge on the rates of gross N transformations in soils of the ICW bed leading to losses of reactive N to the environment. In addition, the kinetics of these processes need to be studied thoroughly for the sustainable use of ICW for removal of excessive N in the treatment of waste waters. Gross N transformation processes were quantified at two soil depths (0–15 and 30–45 cm) in the bed of a surface flow ICW using a 15 N tracing approach. The ICW, located in Dunhill village at Waterford in Southeastern Ireland, receives 500 person equivalent waste waters containing large quantities of organic pollutants (ca. mean annual C, N, P and S contents of 240, 60, 5 and 73 mg L −1 ). Soil was removed from these depths in December 2014 and incubated anaerobically in the laboratory, with either 15 N labeled ammonium (NH4 + ) or nitrate (NO3 − ), differentially labeled with 14 NH4 15 NO3 and 15 NH4 14 NO3 in parallel setups, enriched to 50 atm% 15 N. Results showed that at both soil depths, NO3 − production rates were small, which may have resulted in lower NO3 − reduction by either denitrification or dissimilatory NO3 − reduction to ammonium (DNRA). However, despite being low, the DNRA rates were greater than denitrification rates. Direct transformation of organic N to NO3 −, without mineralization to NH4 +, was a prevalent pathway of NO3 − production accounting for 28–33% of the total NO3 − production. Relative contribution of this process to the total N mineralization was negligible at depth 1 (0.01%) but dominant at depth 2 (99.7%). Total NO3 − production to total immobilization of NH4 + and NO3 − was very small (<0.50%) suggesting that ICW soils are not a source of NO3 − . Despite a large potential of N immobilization existed at both the layers, relative N immobilization to the total N conversion was higher at depth 2 (ca. 2.2) than at depth 1 (ca. 1.5). The NH4 + desorption rate at 30–45 cm was high. However, immobilization in the recalcitrant and labile organic N pools was higher. Mineralization and immobilization of NH4 + processes showed that recalcitrant organic N was the predominant source in ICW soils whereas the labile organic N was comparatively small. Source apportionment of N2 O production showed that the majority of the N2 O produced through denitrification (ca. 92.5%) followed by heterotrophic nitrification (ca. 5.5%), co-denitrification (ca. 1.90%) and nitrification (0.20%). These results revealed that application of a detailed 15 N tracing method can provide insights on the underlying processes of ecosystem based abundances of reactive N. A key finding of this study was that both investigated ICW layers were characterised by large N immobilization which restricts production of NO3 − and further gaseous N losses. Highlights: Production and abundance of nitrate in ICW soils are very small. Immobilization of NH4 + to labile and recalcitrant organic N was prevalent in ICW. Net NH4 + immobilization than desorption makes ICW an NH4 + rich system. Direct oxidation of organic N to nitrate is an important pathway in ICW soils. Recalcitrant form of organic N in ICW was greater than the labile form.